Modeling of human arm movement: a study on daily movement - Choudhury, Tasnuva Tabashhum; Rahman, Md. Mozasser; Khan, Md. Raisuddin; Khorshidtalab, Aida (2013)
Mimicking human arm motion has become a challenging topic for the researchers among the field of Human rehabilitation, motor control and perception, biomechanics, and several other related research topics. Considering human-robot cooperation, this paper is focused on modeling human arm while performing planner motion. In this work human arm is assumed as a mass-spring-damper system and based on this assumption the related mathematical model is developed. The desired movement in this study is one of the daily activities with obstacle. Mathematical model is developed with the help of the robotic principle, mechanical system analysis method, and also with the help of biological data. The kinematic and dynamic data is then analyzed. In this work kinematic data are taken from the ShapTape® device. The different components of the position, velocity and acceleration are compared. Besides, the analysis of the simulated torques is done. MATLAB is used for the simulation. These observations are expected to give several ideas for designing a controller for upper limb exoskeleton for rehabilitation purposes.